A cognitive approach to scent marketing: the effect of odor priming and processing dynamics on consumer aesthetic preferences and choices - De Luca, Ramona (2018)
Academic research on the effect of scent in marketing and consumer behavior have successfully demonstrated how odors improve cognitive, affective, and behavioral responses of consumers in the marketplace. Little attention has been turned to the cognitive mechanism through which scents provide information, and help individuals, and consumers, to attribute a meaning to physical, and psychological phenomena. In this dissertation, I discuss the underlying mechanism through which smell perceptions contribute to consumer decision-making, and preference formation, relying on the connection between smell, cognitive processing, and emotional paths. The dissertation is composed of three articles, which make an initial contribution to scent marketing by exploring the potential of a cognition-based approach to studies on olfaction (Article 1), empirically testing affective and semantic odor priming effects on consumer product and brand choices (Article 2), and empirically demonstrating how olfactory information added to an unscented product contribute to aesthetic preferences formation and processing style (Article 3). In particular, Article 1 consists of a systematic review of the most relevant studies on olfaction published from 1992 to 2017 and presents the current theories and approaches to the investigation of scent effects on consumer behavior, as well as introduces the opportunity of applying a cognitive-based approach to scent marketing studies. The article 2 contributes to olfactory priming literature demonstrating that the incidental exposure to an odor may non-consciously activate information which regulates consumer’s choice of products and brands. Eight experiments demonstrate that odors are primarily perceived through the dimension of their valence and that this process of odor perception and interpretation is an affective-based mechanism (i.e., affective priming) rather than associative-based (i.e., semantic priming). Article 3 explores how olfactory cues added to an unscented product (e.g., pencil) contribute to developing consumers’ aesthetic preferences for the product. I empirically test the PIA Model (Pleasure and Interest Model for Aesthetic Liking) in four experiments and demonstrated that olfactory information is processed across the two routes of heuristic and systematic processing simultaneous, whereas attribute-based information is processed primarily heuristically and then systematically. The final chapter presents the implications that a cognitive-based approach may provide to researchers, managers, and public policies makers to advance in scent marketing theory and practice.